La banca móvil como alternativa para la inclusión social en áreas rurales - Azabache, Carlos (2018)
This paper addresses mobile banking implementation viability in Peru, especially in rural areas. In Peru, people with low levels of income has scarce access to formal banking services, not only because of economic disparity, but also as a result of market gaps related to these services. This paper gathers data from FITEL projects, and develops an empirical analysis from which it can be concluded that mobile banking in Peru is possible and would help to reduce the aforementioned deficiencies.